Epigenetics in Personality Disorders: Today's Insights - Gescher, Dorothee Maria; Kahl, Kai G.; Hillemacher, Thomas; Frieling, Helge; Kuhn, Jens; Frodl, Thomas (Frontiers in Psychiatry, 2018)
Objective: Epigenetic mechanisms have been described in several mental disorders, such as mood disorders, anxiety disorders and schizophrenia. However, less is known about the influence of epigenetic mechanisms with regard to personality disorders (PD). Therefore, we conducted a literature review on existing original data with regards to epigenetic peculiarities in connection with personality disorders. Methods: Systematic literature review using PRISMA guidelines. Search was performed via NCBI PubMed by keywords and their combinations. Used search terms included “epigenetic,” “methylation,” “acetylation” plus designations of specified personality traits and disorders according to DSM-IV. Results: Search yielded in total 345 publications, 257 thereof with psychiatric topic, 72 on personality disorder or traits, 43 of which were in humans and epigenetic, 23 thereof were original studies. Lastly, 23 original publications fulfilled the intended search criteria and were included. Those are 13 studies on gene methylation pattern with aggressive, antisocial and impulsive traits, 9 with borderline personality disorder (BPD), and 2 with antisocial personality disorder (ASPD). The results of these studies showed significant associations of PD with methylation aberrances in system-wide genes and suggest evidence for epigenetic processes in the development of personality traits and personality disorders. Environmental factors, of which childhood trauma showed a high impact, interfered with many neurofunctional genes. Methylation alterations in ASPD and BPD repeatedly affected HTR2A, HTR3A, NR3C1, and MAOA genes. Summary: Epigenetic studies in PD seem to be a useful approach to elucidate the interaction of co-working risk factors in the pathogenesis of personality traits and disorders. However, the complexity of pathogenesis leads to divergent results and impedes an explicit interpretation. Differing methylation patterns within the selected PD could indicate subgroups which would benefit from patient-oriented therapeutic adjustments. They might play a major role in the future design and observation of early therapeutic intervention and thus could help to prevent severe dysfunctional conduct or full-blown personality disorder in risk subjects.